Analisa Perbandingan Metode MAUT dan WASPAS Dalam Menentuan Tempat Pelatihan Kursus Computer Terbaik - Mochamad Dedy Subekti Rahardjo (Bulletin of Computer Science Research, 2024)
This study aims to analyze the comparison of two multi-criteria decision-making methods, namely Multi-Attribute Utility Theory (MAUT) and Weighted Aggregated Sum Product Assessment (WASPAS) in determining the best computer course training place. The background of this study is based on the need to choose a training place that is in accordance with various important criteria such as teacher quality, facilities, costs, and institutional reputation, which often cause difficulties in decision making. The main problem faced is how to choose the most effective and efficient method in providing accurate results according to user preferences. For this reason, the two methods are compared based on their ability to process multi-criteria data by considering the weight and utility of each alternative. This study uses a quantitative approach by collecting data from several computer course places in a certain area and applying both methods to assess the performance of each place. Thus, the final ranking results show consistency in choosing the best alternative. The Multiicom alternative (AT5) is ranked first in both methods, with a value of 0.940 in the MAUT Method and 0.962 in WASPAS.